Lutzomyia migonei as putative vector of visceral leishmaniasis in La Banda, Argentina - Salomón, Oscar Daniel (2010)
Four autochthonous cases of human visceral leishmaniasis (VL) were reported in La Banda, Santiago del Estero from June 2007 to May 2008. In the vicinity of these cases there were 3/47 rK39 sero-positive dogs, and another 4 dogs with VL were reported by passive surveillance. The sero-positive dogs and infected humans lived within a 3.1 km radius. Phebotomine sand fly captures were performed twice during November/December 2007 and April 2008. In 20 of the 59 sampled sites in the areas of the human and canine cases (220 night/traps) 151 phlebotomine sand flies were collected and consisted of: Lutzomyia migonei 93%, Lutzomyia cortelezzii 5.6% and Lutzomyia neivai 1.4%. We propose that there was an enzootic cycle of VL with accidental human transmission due to L. migonei and suggest that there be a surveillance of human isolated cases of VL within the L. migonei dispersion area.